“La gestión de la información en el departamento de nivelación en la Universidad Técnica de Cotopaxi 2023 - Inca Lema, Edison Stalin (2024)
The study on “Information Management in the Remedial Department at Technical University of Cotopaxi 2023” focuses on the quantitative evaluation of information management practices, using a non-experimental design. The research was based on data collection through surveys with a questionnaire as the instrument. The main objective of the research was to propose strategies to improve information management. To achieve this purpose, data were systematically collected from department members. Data were structured around key aspects related to information management, such as collection, storage, processing, and access to information. The results provided a detailed insight into the current information management practices in the remedial department, identifying areas of strength and weakness in its handling. Based on these findings, specific strategies were proposed to enhance efficiency and effectiveness of management in the department. In summary, the study evaluated the current situation of information management in the remedial department of Technical University of Cotopaxi, at the same time, it offers strategies for optimization.